Metacognitive myopia and the overutilization of misleading advice - Fiedler, Klaus; Hütter, Mandy; Schott, Malte; Kutzner, Florian (Journal of behavioral decision making, 2019)
Previous research on advice taking has explained the failure to exploit collective wisdom in terms of the egocentric underweighting of advice provided by independent others. The present research is concerned with an opposite and more radical source of irrational advice taking, namely, the failure to critically assess the validity of advice due to metacognitive myopia. Participants could use the advice of one or two experts when estimating health risks. They read sketches of the study samples that experts had drawn to estimate conditional probabilities (e.g., of HIV‐given drug addiction). Whether samples were valid or seriously biased, subsequent judgments were strongly affected by any advice (Experiment 1). Uncritical reliance on any advice persisted when participants were sensitized to the contrast of valid and invalid advice in a repeated measures design (Experiment 2), when participants themselves believed advice not to be valid (Experiment 3), and even after full debriefing about invalid advice (Experiment 4). Lay advice exerted a similar influence as expert advice (Experiment 5). Although these provocative results are independent of numeracy and consensus (Experiment 6), they highlight the impact of metacognitive myopia as an impediment of social rationality.